Antennal sense cone variation in Teuchothrips species of New Caledonia, with one new generic combination (Thysanoptera, Phlaeothripinae) - Mound, Laurence A.; Goldarazena, Arturo (Zootaxa, 2022)
Four species of Teuchothrips are recognised as endemic to New Caledonia and distinct from the many species of this genus in Australia. Three of these species are shown to have a variable number of sense cones on antennal segment IV, in contrast to most recorded species in the Liothrips-lineage. One endemic species is removed from Teuchothrips and considered here as Neocecidothrips pacificus (Bianchi) comb.n. together with illustrations and diagnostic notes. A key is provided for the four Teuchothrips species known from New Caledonia.